2007
DOI: 10.1103/physrevlett.99.147007
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Quasi-Long-Range Order below the Bragg Glass Transition

Abstract: We report small angle neutron scattering rocking-curve measurements of the flux line lattices in the peak effect region in a niobium single crystal. It is found that upon cooling in a magnetic field, the transverse orientational order as well as the longitudinal translational order grow rapidly with decreasing temperature, indicating diminishing population of defects in the ordering vortex matter. Surprisingly, during subsequent warming, longitudinal order increases with increasing temperature, presumably due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…As already discussed, energy barriers may trap the VL in disordered metastable configurations when cooling from the normal state in a constant field. In addition to a transport current or an AC field, an ordering of the VL can in some cases be achieved by a simple thermal cycling (Daniilidis et al, 2007;Marziali Bermudez et al, 2017). Conversely, the application of a field oscillation will introduce an edge "contamination" of the VL at surfaces where vortices enter and leave the sample (Hanson et al, 2011).…”
Section: Relating Structural and Dynamic Propertiesmentioning
confidence: 99%
“…As already discussed, energy barriers may trap the VL in disordered metastable configurations when cooling from the normal state in a constant field. In addition to a transport current or an AC field, an ordering of the VL can in some cases be achieved by a simple thermal cycling (Daniilidis et al, 2007;Marziali Bermudez et al, 2017). Conversely, the application of a field oscillation will introduce an edge "contamination" of the VL at surfaces where vortices enter and leave the sample (Hanson et al, 2011).…”
Section: Relating Structural and Dynamic Propertiesmentioning
confidence: 99%
“…The computed function slightly overestimates the width of the actual resolution function. For example, the rocking curves of an ordered FLL in niobium, obtained under the conditions introduced in our calculation, have half width of 1.2 mrad (Daniilidis et al, 2007), which is approximately 87% of the width of the numerical integration result (1.38 mrad). This discrepancy is a result of the assumptions made in our calculation.…”
Section: Numerical Evaluation Of the Resolution Functionmentioning
confidence: 74%
“…We performed SANS rocking-curve measurements on an FLL in a niobium single crystal on the NG-3 instrument at NCNR-NIST. The experimental findings are reported in detail elsewhere (Daniilidis et al, 2007). Here we compute the resolution function starting from the instrumental configuration and compare the result with experimentally obtained curves which are at the resolution limit.…”
Section: Numerical Evaluation Of the Resolution Functionmentioning
confidence: 91%
“…Since the vortex lattice is embedded in an atomic lattice, neutron scattering (Furrer et al, 2009) is the only technique for direct structural studies. There have been several attempts (Klein et al, 2001;Daniilidis et al, 2007;Laver et al, 2008) to observe the Bragg glass phase, but no conclusive evidence has been found even though there are compelling arguments (Klein et al, 2001) for why one would not be able to measure it directly.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the vortex states in bulk Nb samples have been studied extensively (Schelten et al, 1971;Christen et al, 1977;Rosov et al, 1994;Ling et al, 2001;Forgan et al, 2002;Daniilidis et al, 2007;Laver et al, 2008). These small-angle neutron scattering (SANS) measurements revealed the bulk properties of the interior of the samples.…”
Section: Introductionmentioning
confidence: 99%